Nigeria : a regenerative economy or vegetative existence? : 1985 alumni lecture - Marinho, F. R. A. (Ibadan: Nigerian National Petroleum Corp., 1985)
This volume provides the details of an alumni lecture delivered by F.R.A. Marinho, then Managing Director Nigerian National Petroleum Corporation (NNPC) at the Conference Centre, University of Ibadan, on Friday, 14th June 1985.
lje 5/3/19
Arch
Keywords: Economic development; Economic growth; Economic history; Economic policy; Nigeria